Proses Pembuatan Mediapembelajaran Dudukan Mesin Perombakan - Aries Mulyana Rifa’i (Prosiding, 2022)
Making learning mediafor the remodel machine holder with the formatiion of hollow materials,pipes, plates, iron axles and scaffolding wheels that will be designed in such away, The purpose of this practical work is to find out the design of the engine overhoul stand, which refers to the manufacture of learning media for the overhaul machine holder. The method that will be used is the procces of observing, summarizing qnd recording data from the head of the light vehicle engineering study program. In a design, the first thing is to design a tool in the form of an image. The design is obtainedbased on the results of instrument observations and then modified so that the results of a good image design. The image design uses Solidworks 2017 software. The results of the simulation on the product modeling are stress, displacement, safety factor (FOS), and shear force. After carrying out practical work on the design of the overhaul machine holder on the Solidworks application, it can be concluded that the design determines the manufacture of learning media for the overhaul machine holder.